Strike-slip pattern of the Maidan fault along the southern margin of the Central Tianshan revealed by InSAR and GNSS observations - Xiaohang Wang; Caijun Xu; Yangmao Wen; Jie Li; Wei Xiong; Jiuyuan Yang; Shuai Wang; Guangyu Xu; Shanshan Li (Geo-spatial Information Science)
Observations of present-day surface deformation are crucial for assessing the long-term seismic hazard of active faults. In this study, we used a high-precision deformation field derived from the integration of global navigation satellite system (GNSS) and interferometric synthetic aperture radar (InSAR) data to systematically investigate the strike-slip behavior of the entire Maidan Fault (MDF). Our results show that the MDF exhibits a clear sinistral strike-slip pattern: the western segment has a relatively higher slip rate of approximately 3.1–3.5 mm/yr, while the eastern segment shows a lower rate of around 2.0 mm/yr. We find that the MDF primarily accommodates the sinistral shear component induced by the clockwise rotation of the Tarim Basin in the Central Tianshan (CTS), accounting for more than half of the total sinistral motion in the region. In addition, by integrating historical earthquake records, we find that although the western segment of the MDF lacks significant historical seismicity, its relatively high slip rate and strong locking characteristics indicate an elevated seismic risk, highlighting the need for continued attention and monitoring.